A case of sigmoid colon perforation presenting with pneumomediastinum. Issue 12 (17th December 2019) - Kuroda, Yukihito; Hisakura, Katsuji; Akashi, Yoshimasa; Enomoto, Tsuyoshi; Oda, Tatsuya
Abstract: A 62-year-old woman had developed polymyositis 12 years previously and had taken oral steroids. Chest and abdominal computed tomography showed pneumomediastinum and free air in the abdominal cavity. Although a colon perforation was suspected, the perforation site could not be identified on the image. In addition, a diagnosis of oesophageal rupture could not be excluded from the findings of pneumomediastinum. After general anaesthesia, an upper gastrointestinal endoscopy was performed before surgery. Because there was no obvious perforation in the oesophagus, a laparotomy approach was used. A perforation was found on the mesentery side of the sigmoid colon, and a perforation of the sigmoid colon's diverticulum towards the mesentery was diagnosed. A Hartmann's procedure was performed. Colon perforations are rarely associated with pneumomediastinum. Preoperative endoscopy is useful to help diagnose and determine the surgical procedure if an obvious perforation cannot be identified.